Efficient organization of production: Nested versus horizontal outsourcing - Oz Shy; Rune Stenbacka (Federal Reserve Bank of Boston, 2009)
The authors characterize equilibrium and efficient modes of production by comparing nested (vertical) outsourcing with horizontal outsourcing. Nested outsourcing is found to be inefficient unless the cost of monitoring outsourced production lines increases sharply with the number of subcontractors and not only with the number of outsourced components. They characterize a market failure in which nested outsourcing is selected when the case dictates that horizontal outsourcing is the efficient outsourcing mode. This failure occurs at an intermediate range of the costs of monitoring outsourcing to several subcontractors.
Keywords: D2; L2; L24; 330; outsourcing; subcontracting; nested outsourcing; horizontal outsourcing; efficient organization of outsourcing; Outsourcing; Lieferant; Wirtschaftliche Effizienz; Theorie